2011
DOI: 10.1016/j.jana.2011.08.003
|View full text |Cite
|
Sign up to set email alerts
|

The Need for Anal Dysplasia Screening and Treatment Programs for HIV-Infected Men Who Have Sex With Men

Abstract: Anal cancer rates, which were higher for men who have sex with men (MSM) compared to the general population before HIV, increased dramatically after the HIV epidemic began and continue to increase in HIV-infected MSM despite the advent of antiretroviral therapy and associated immune reconstitution. Because of the similarity to cervical cancer and an established link to human papillomavirus infection, many experts have called for widespread implementation of anal cytological screening and treatment programs, es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 52 publications
(60 reference statements)
0
3
0
Order By: Relevance
“…This educational activity addresses an established need (10,15,14) for training on anal cancer in a group of health care professionals. Our study evidences a lack of knowledge about this topic among the medical students, residents and faculty, and the need for future training in this area in PR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This educational activity addresses an established need (10,15,14) for training on anal cancer in a group of health care professionals. Our study evidences a lack of knowledge about this topic among the medical students, residents and faculty, and the need for future training in this area in PR.…”
Section: Discussionmentioning
confidence: 99%
“…Future training activities should expand these objectives and provide more in-depth education to additional populations of health care professionals in PR, given that one issue for the implementation of anal cancer screening and treatment programs is that sufficient health care personnel must be available to perform detection and treatment procedures (15). Thus, these trained professionals will be instrumental to the prevention and control of anal disease.…”
Section: Discussionmentioning
confidence: 99%
“…Routine screening for AIN in individuals at high risk such as PLWH or MSM is controversial, because randomized controlled trials showing that such screening programs are efficacious at reducing anal cancer incidence and mortality are lacking, whereas the potential benefits are quite large. [46][47][48][49][50][51][52] Systematic reviews and meta-analyses have suggested that anal cytology is effective in detection of AIN, particularly for individuals at high risk. [53][54][55] Most guidelines do not recommend anal cancer screening even in people at high risk at this time or state that there may be some benefit with anal cytology.…”
Section: Risk Reductionmentioning
confidence: 99%